2014
DOI: 10.1186/s12917-014-0301-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with embryonic stem-like cells into osteochondral defects in sheep femoral condyles

Abstract: BackgroundArticular cartilage has poor intrinsic capacity for regeneration because of its avascularity and very slow cellular turnover. Defects deriving from trauma or joint disease tend to be repaired with fibrocartilage rather than hyaline cartilage. Consequent degenerative processes are related to the width and depth of the defect. Since mesenchymal stem cells (MSCs) deriving from patients affected by osteoarthritis have a lower proliferative and chondrogenic activity, the systemic or local delivery of hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 87 publications
(123 reference statements)
2
22
0
Order By: Relevance
“…However, a major limiting factor to using adult mesenchymal stem cells for cartilage repair in the clinic has been the variable capacity of somatic cells to regenerate permanent cartilage , . To this end, various groups have explored the use of pluripotent stem cells for cartilage repair , , , , . Specifically, multiple methods have been proposed to derive chondrocytes from human embryonic and induced pluripotent stem cells , .…”
Section: Discussionmentioning
confidence: 99%
“…However, a major limiting factor to using adult mesenchymal stem cells for cartilage repair in the clinic has been the variable capacity of somatic cells to regenerate permanent cartilage , . To this end, various groups have explored the use of pluripotent stem cells for cartilage repair , , , , . Specifically, multiple methods have been proposed to derive chondrocytes from human embryonic and induced pluripotent stem cells , .…”
Section: Discussionmentioning
confidence: 99%
“…Gotterbarm et al [25] showed that 6.3 mm diameter OCD did not spontaneously heal in mini-pig, confirming the applicability of this pig breed to articular cartilage research. e large majority of the cartilage regeneration studies in the mini-pig are performed on the joint knee, involving the medial [66] or femoral condyles [67,68], or femoral trochlea. Generally, 6 mm to 8 mm diameter or larger dimensions OCD are created, and the postoperative follow-up period is usually between 3 and 24 months (Table 5).…”
Section: Pigmentioning
confidence: 99%
“…e cartilage thickness of the medial femoral condyle is approximately 0.45 mm. e location of the cartilage defects in the sheep model has involved the medial femoral condyle [67,70,71], both femoral condyles [72,73], and the femoral trochlea [70]. OCD with a diameter of 6-8 mm and a depth of 5-13 mm were used for the assessment of biomaterial strategies ( Table 6).…”
Section: Sheepmentioning
confidence: 99%
“…(25) When allogenic ESCs seeded in fibrin glue were applied for treating induced knee focal osteochondral defects in sheeps, these were efficiently repaired with better outcomes (higher collagen II and proteoglycans) than the untreated control joints. (26) While promising, ESCs are associated with ethical concerns surrounding their derivation, limiting their use. (27) This has promoted significant interest in adult-derived stem cells such as MSCs, a multipotent cell population and precursor of cartilage.…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…Most of these studies suggest promising results with improved cartilage regeneration between 3 months and 2 years. 26,[32][33][34][35][36] Significant superior histologic evidence of cartilage regeneration when using hydrogels are reported when compared to empty defects. The cell sources, collection techniques, cell processing, qualitative and quantitative characterizations, and delivery methods vary widely between studies.…”
Section: Preclinical Animal Modelsmentioning
confidence: 99%